Can Individuals with Down Syndrome Benefit from Hippotherapy? An Exploratory Study on Gait and Balance. (17th August 2020) - Portaro, Simona; Cacciola, Alberto; Naro, Antonino; Cavallaro, Filippo; Gemelli, Gaetano; Aliberti, Barbara; De Luca, Rosaria; Calabrò, Rocco Salvatore; Milardi, Demetrio
ABSTRACT: Purpose : To evaluate whether a hippotherapy protocol may influence balance and gait in patients with Down Syndrome (DS). Methods : Fifteen male patients affected by DS underwent a 6-month hippotherapy protocol. Stabilometric, baropodometric, and gait assessments were performed at baseline (T0 ) and at the end of the treatment (T1 ). Results : At baseline, DS patients showed a low bilateral hind foot pressure percentage at the baropodometric analysis, a high center of pressure area in the closed-eye condition, a high center of pressure sway in open- and closed-eyes recordings, a high medio-lateral and antero-posterior velocity oscillations in the closed eye condition, and a reduced step-length and velocity. After the 6-month, hippotherapy protocol, DS patients had a significant bilateral higher hindfoot pressure percentage. The stabilometric analysis revealed a lower center of pressure area in the closed-eye condition, and a significantly reduced center of pressure sway in open- and closed-eyes recordings. In addition, DS patients showed lower medio-lateral and antero-posterior velocity oscillations in the closed eye condition. Finally, hippotherapy significantly improved step length and velocity. Conclusions : This pilot study demonstrates that hippotherapy determines functional improvement in gait speed, width, bilateral symmetry, and balance in DS.